(untitled) (Palíndromo, 2014)
This work is the result of a study of semiotic Cup mascot of Fédération Internationale de Football Association (FIFA) to be held in Brazil in 2014, inspired by the animal Tatu-ball, aiming an understanding of it in their semantic aspects. The choice of such a character is due to its large current evidence in the media, have been chosen by the Brazilian representative at the next World Cup and the controversy that has arisen around the fact. The methodology comprises the steps of identifying key elements in the analysis of the same character according to the relevant literature presented throughout the article. Finally, the objective is a clarification if the picture Mascot Tatu-ball provides information graphic-visual and semiotic enough for the audience to understand as such.